1972
DOI: 10.1161/01.res.31.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Afferent Activity of Canine Aortic and Sinus Nerves

Abstract: Pressure-dependent changes in afferent activity in the aortic and the sinus nerves were studied in 17 anesthetized dogs that were artificially ventilated with oxygen. Systemic arterial blood pressure was varied either continuously or in steps over the range of mean aortic blood pressure from 220 to 50 mm Hg with a pressurized reservoir connected to the abdominal aorta. Multifiber preparations from 20 aortic and 8 sinus nerves were used, and stimulusresponse curves were defined by measuring the mean impulse fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
1
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 24 publications
6
42
1
1
Order By: Relevance
“…According to reports by Thoren et al [22] and Brown et al [33,34], the regularly discharged myelinated fibers tend to respond well to the peak pressure of the sine wave and may be of major importance to cardiovascular control during decreases in arterial pressure. The pressure-aortic nerve discharge curves in systole of the present study showed an s-shape, remarkable changes during decreases in arterial pressure in all 3 groups, and were similar to results in canine aortic nerves that were obtained by depressing pressure from the maximal level to the threshold level in the study of Pelletier and colleagues [35]. The pressure-aortic nerve discharge curve in the HDT group did not fit that of the other 2 groups at threshold level, and the maximal decrease of aortic nerve activity in the HDT group was less than in both groups.…”
Section: Discussionsupporting
confidence: 90%
“…According to reports by Thoren et al [22] and Brown et al [33,34], the regularly discharged myelinated fibers tend to respond well to the peak pressure of the sine wave and may be of major importance to cardiovascular control during decreases in arterial pressure. The pressure-aortic nerve discharge curves in systole of the present study showed an s-shape, remarkable changes during decreases in arterial pressure in all 3 groups, and were similar to results in canine aortic nerves that were obtained by depressing pressure from the maximal level to the threshold level in the study of Pelletier and colleagues [35]. The pressure-aortic nerve discharge curve in the HDT group did not fit that of the other 2 groups at threshold level, and the maximal decrease of aortic nerve activity in the HDT group was less than in both groups.…”
Section: Discussionsupporting
confidence: 90%
“…5) suggests that in man extracarotid baroreceptors influence sympathetic activity at normal blood pressure levels. This would be in contrast to findings in dogs, in which the aortic arch receptors seem to be brought into action mainly when blood pressure is higher than normal (Donald & Edis, 1971;Edis, 1971;Pelletier, Clement & Shepherd, 1972).…”
Section: Discussioncontrasting
confidence: 90%
“…In particular, vagotomy partially interrupts aortic arch baroreceptor firing; however, given the relative importance of aortic compared with carotid sinus baroreceptors in circulatory regulation at non-hypertensive pressures (Donald & Edis, 1971;Edis, 1971;Dampney, Taylor & McLachlan, 1971;Pelletier, Clement & Shepherd, 1972) it seems probably that aortic arch afferents have only a minor role to play in the changes seen.…”
Section: Discussionmentioning
confidence: 99%